"Please Q!" : a study on queuing and its negotiated order in Singapore - Ong, Yee Yen (2015)
This paper seeks to study on the queues in Singapore by understanding how Singaporeans perceive and negotiate social order in their everyday waiting lines. Drawing upon the ideas of symbolic interactionism and the works of Strauss (1979) on the ‘negotiated order’, the social order of queues in this nation were critically examined through individuals’ interaction and negotiation with one another. The research is based on in-depth interviews with 14 young Singaporeans, and field experiments at 3 different fast food outlets' queues in Singapore. From the findings, I argued that negotiation is inevitable in all queuing instances so as to establish order. Successful queue-formation is made possible only through the negotiation of the collective ‘worked-out agreement’ of queues. In the event of a queue intrusion, individuals will engage in acts of (re)negotiation to (re)establish order. In this process, I argued that ‘impression management’ and the identity of the intruder should not be discounted.